Effect of organic N-halamines on selected membrane functions in intact Staphylococcus aureus cells. - Williams, D E (1991)
Two N-halamine compounds, 3-chloro-4,4-dimethyl-2-oxazolidinone and 1,3-dichloro-4,4,5,5-tetramethyl-2-imidazolidinone, were compared with free chlorine as to their effects on selected membrane functions of intact Staphylococcus aureus cells. Free chlorine was found to cause a loss of permeability control, as measured by the efflux of potassium from the cells and a dramatic increase in hydrogen ion permeability, and to affect cell respiration in a nonreversible fashion, as measured by oxygen uptake. The two N-halamines were found to have very little effect on permeability to either potassium or hydrogen ions but were both found to dramatically inhibit respiration in a reversible manner. It is proposed that the first step in the disinfection process by these N-halamines is an inhibition of respiratory enzymes that, if not reversed, ultimately leads to a loss of cell viability.